Increasing Accessibility to Academic Support in Higher Education for Diverse Student Cohorts - Bornschlegl, Madeleine; Caltabiano, Nerina Jane (Teaching and Learning Inquiry, 2022)
Academic support at Australian universities has become an important aspect of higher education, as student cohorts continue to diversify, and universities need to ensure the students’ success and the institutions’ reputations. Often, students in need do not access academic support services and little is known about what influences students’ decisions to seek academic support. This small-scale qualitative study aims to clarify why students (do not) engage in support and what could be changed to make services more accessible and engaging. Semi-structured interviews revealed that the promotion of services needs to be improved and public stigma about seeking academic help should be addressed to normalise accessing academic support services at university. A high standard of ease of use and the opportunity to participate in support in various modes (e.g. online, face-to-face, peer learning, individual learning) contribute to the helpfulness and the overall positive perception of academic support services.